All Star : Student book with audio highlights / Linda Lee, Kristin Sherman, Stephen Sloan, Grace Tanaka, Shirley Velasco. 4, 3 - Lee, Linda
All-Star is four-level, standards-based series for Enghlish learners featuring a picture-dictionary approach to vocabulary building.